Deciphering the Role of Oxygen Vacancies on Structural, Electrical, and Magnetic Properties of Fe‐Substituted Strontium Titanate. Issue 8 (7th May 2018) - Sarin, Neha; Mishra, Monu; Gupta, Govind; Arora, Manju; Luthra, Vandna
Abstract : A comprehensive investigation of incorporation of Fe into SrTiO3 is reported. SrFe x Ti1− x O3−δ ( x  = 0.0 – 0.3) powders are prepared via solid state route. X‐ray diffraction (XRD) and X‐ray photoelectron spectroscopy (XPS) techniques are used to analyze the phase formation, surface chemistry, and electronic structure while scanning electron microscope (SEM) is employed to investigate the surface morphology and microstructural properties. The electrical and magnetic properties are studied at room temperature (RT) to explore the effect of iron substitution on the current conduction and magnetic phase transformation. XPS results indicate the presence of mixed valence state as Fe content increased resulting in considerable enhancement of oxygen vacancies. Moreover, a continuous decrease in Fermi level (FL) is observed as Fe concentration is increased. The increment in Fe concentration leads to variation of current–voltage ( I–V ) characteristics from linear to non‐linear. Magnetic measurements demonstrate three behaviors; an intrinsic diamagnetic behavior ( x  = 0.0, 0.05) followed by ferromagnetic behavior ( x  = 0.1, 0.2), and finally a paramagnetic behavior ( x  = 0.3) due to transition metal impurities and defects. These studies have been used to establish correlation between the evolution of oxygen vacancies emanating from Fe‐substitution on structural, electrical, and magnetic properties. Abstract : This paper reports the exhaustive investigation of SrFex Ti1−x O3 (x = 0.0 ‐ 0.3) network. The effect of increasing Fe doping concentration and evolution of oxygen vacancies on structural, electrical and magnetic properties has been discussed. The presence of mixed valence state (Fe 3+ and Fe 4+ ) along with considerable increase of oxygen vacancies on doping was investigated.